Should I Stay or Should I Go? Analysing Returnee Overseas Filipino Workers’ Reintegration Measures Given the COVID-19 Pandemic - Opiniano, Jeremaiah (Archīum Ateneo, 2023)
The paper sought to determine if the varied forms of assistance to returnee overseas Filipino workers (OFWs) during this COVID-19 pandemic prompt them to stay home or return overseas. This mixed methods study combined a logistic regression of a large-scale survey of returnee migrant workers (N = 8,266, done by the International Organization for Migration) and a documentary analysis of efforts by the Philippines to assist returnees. It was found that the Philippine government's migration and non-migration agencies have laid out the red carpet to provide multifarious economic and non-economic forms of assistance to returnee OFWs. However, logistic regression results reveal that in spite of business capital, skills training and income support given to returnees, amount differentials between local and overseas earnings plus pandemic-induced income disruptions propel their desires to repeat their overseas labour migration. The paper methodologically contributes the logical connection between logistic regression results with the running documented efforts of the Philippine government for returnees as part of that Southeast Asian country's overall COVID-19 containment strategy. Meanwhile, as overseas work and remittances provide enduring solutions for returnees and their families to move forward from the COVID-19 pandemic, the Philippine government's instrumentalities may have to reconfigure the country's overall approach to migrant reintegration.